ChemInform Abstract: Mukaiyama Reagent/NaNO2/Wet SiO2 as a Mild and Heterogeneous Reagent System for the N‐Nitrosation of Amines and Preparation of Azides from Hydrazines. Issue 4 (January 2016) - Azadi, Roya; Kolivand, Khatereh
Abstract: The simple protocol allows the nitrosation under mild conditions to give nitrosamines and azides in high yields.